2021
DOI: 10.21203/rs.3.rs-912920/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Are solution processed CsPbI3 perovskite nanocrystalline films similar to traditional crystalline semiconductors?

Abstract: We use ultrafast photocurrent spectroscopy with a sub-25 picosecond resolution to address a long-standing question in emergent perovskite materials: are solution-processed CsPbI3 perovskites nanocrystal films similar to their counterparts semiconductors including GaAs and Si? Prior to carrier trapping, all semiconductors show similar transition of transport mechanism from the band-like transport due to the longitudinal optical (LO) phonon scattering in the higher temperature region to a combination of band-lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…The tted coef-cient b value indicates the strength of the carrier-phonon coupling. 61 The b values in the range of −1.12 ∼ −1.56 indicate that the phonon scattering dominates the carrier mobility in the entire temperature range (Fig. 5f), which is consistent with the physical mechanism in which the inuence of impurity scattering is only shown at very low temperatures.…”
Section: Temperature-dependent Optical and Electronic Propertiessupporting
confidence: 81%
“…The tted coef-cient b value indicates the strength of the carrier-phonon coupling. 61 The b values in the range of −1.12 ∼ −1.56 indicate that the phonon scattering dominates the carrier mobility in the entire temperature range (Fig. 5f), which is consistent with the physical mechanism in which the inuence of impurity scattering is only shown at very low temperatures.…”
Section: Temperature-dependent Optical and Electronic Propertiessupporting
confidence: 81%
“…[174] Interestingly, very recent work by Gao and colleagues shows that CsPbI 3 PQDs exhibit the strongest carrier-longitudinal optical phonon interaction among all traditional semiconductors. [175] Lastly, it is known that the efficiency of the emerging perovskite solar cells is typically limited by the nonradiative recombination that occurs at the interface between absorber and charge transport layer. [176] However, Wieliczka et al recently reported that the interfaces between the PQD absorber and the charge transport layers have no signi ficant impact on recombination losses, and the free charge carrier concentration of PQDs is orders of magnitude higher than that of perovskite thin films.…”
Section: Wwwadvmatde Wwwadvancedsciencenewscommentioning
confidence: 99%
“…[ 174 ] Interestingly, very recent work by Gao and colleagues shows that CsPbI 3 PQDs exhibit the strongest carrier‐longitudinal optical phonon interaction among all traditional semiconductors. [ 175 ] Lastly, it is known that the efficiency of the emerging perovskite solar cells is typically limited by the nonradiative recombination that occurs at the interface between absorber and charge transport layer. [ 176 ] However, Wieliczka et al.…”
Section: Scale‐up Of Pqd Solar Cellsmentioning
confidence: 99%